Takotsubo Cardiomyopathy Caused By Acute Ischemic Stroke. - Tahir, Hassan; Hussain, Khandakar; Ullah, Saad (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Takotsubo cardiomyopathy, also known as stress cardiomyopathy, usually occurs secondary toextreme physical and emotional stress. Subarachnoid hemorrhage has been strongly related tostress cardiomyopathy due to catecholamine surge in such patients; however, ischemic stroke hasbeen rarely associated with takotsubo cardiomyopathy. Whether ischemic stroke is the cause orthe result of takotsubo cardiomyopathy is difficult to ascertain in some cases. We present a caseof a 78-year-old female who came with stroke symptoms and developed cardiogenic shocksecondary to takotsubo cardiomyopathy.